Austenitic stainless steel
By optimizing the alloy composition and heat treatment process of austenite stainless steel, the problems of insufficient yield strength and surface properties are solved, and austenite stainless steel with high strength, high ductility and good surface properties are achieved, which is suitable for structural components.
Patent Information
- Application Number
- CN202380037026.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-29
- Filing Date
- 2023-03-10
- Publication Date
- 2024-12-20
AI Technical Summary
The existing austenitic stainless steel has insufficient yield strength in structural applications, and the conventional flat rolling process increases costs and deteriorates the elongation of the material, making it difficult to achieve the optimization of hardness, ductility and surface properties at the same time.
By controlling the alloy composition and heat treatment processes of austenitic stainless steel, including hot rolling, hot annealing, cold rolling and cold annealing, ensure that the average grain size is between 3 μm and 10 μm, and the martensite fraction and orientation difference angle reach a specific range , and optimize the alloy element ratio through electron backscattering and diffraction analysis to achieve high intensity, high ductility and good surface properties.
Austenitic stainless steel in the thickness range of 0.4-2.0mm has excellent hardness, high strength-high ductility and good bending molding. There are no surface cracks in the bending parts and low surface roughness, which are suitable for structural components.
Smart Images

Figure CN119173648A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an austenitic stainless steel having improved hardness, high strength-high ductility, drawability, bendability and surface property characteristics. Background Art
[0002] Generally, austenitic stainless steel has excellent formability, work hardening and weldability, and is therefore used in various applications such as transportation parts and construction parts. However, the yield strength of 304 series stainless steel or 301 series stainless steel is only at the level of 200-350MPa, so there are limitations in the application of structures. Therefore, in order to obtain a higher yield strength in general 300 series stainless steel, the conventional method is to use a temper rolling process. However, the method using the temper rolling process has the problem of increased cost and extremely poor elongation of the material.
[0003] Patent document 0001 discloses a method for manufacturing 300 series stainless steel, wherein the 300 series stainless steel is used for laser metal shielding in photoetching processing. In the manufacturing method, a cold annealed material is flat-rolled and then subjected to two stress relief (SR) heat treatments to manufacture the 300 series stainless steel. The 300 series stainless steel has little warping even after half-etching. However, Patent Document 0001 is a manufacturing technology for controlling etching properties and warping after etching, and does not include technical content for structural parts with a thickness of 0.4-2.0 mm. In addition, the Austenitic Stability Parameter (ASP) value calculated based on Md30(℃)=497-462×([C]+[N])-9.2×[Si]-8.1×[Mn]-13.7×[Cr]-20×[Ni]+[Cu]-18.7×[Mo] has a range of 30 to 50. Therefore, the strain-induced martensitic phase transformation occurs too quickly during forming such as tensile testing, resulting in a problem of reduced elongation.
[0004] Patent document 0002 proposes a method of performing a long-term heat treatment at 600-700°C for more than 48 hours to obtain an average grain size of 10 μm or less. However, the method proposed in Patent document 0002 has the problem of reduced productivity and increased manufacturing cost when implemented in an actual production line.
[0005] (Prior art literature)
[0006] Patent Document 0001: International Patent Publication No. 2016-043125A1 (Publication Date: March 14, 2016)
[0007] Patent Document 0002: Japanese Patent Publication No. 2020-050940A (Publication Date: April 2, 2020) Summary of the invention
[0008] 1. Technical issues to be resolved
[0009] The object of the present invention for solving the above-mentioned problems is to provide an austenitic stainless steel having no surface cracks in the bent part and excellent surface roughness by proposing an ultrafine grain manufacturing technology that achieves hardness, high strength-high ductility, drawability, bendability and good surface properties of the bent part.
[0010] (II) Technical solution
[0011] The austenitic stainless steel according to one embodiment of the present invention may contain, in terms of weight %, 0.04-0.07% C, 0.3-0.6% Si, 0.5-1.5% Mn, 0.1-0.4% Cu, 0.05-0.2% Mo, 8.0-9.0% Ni, 18.0-19.0% Cr, and 0.02-0.05% N, and may contain the remainder of Fe and inevitable impurities, and the Σ value of the austenitic stainless steel represented by the following formula (1) may be 180 or more and 240 or less.
[0012] Formula (1): Σ = 105 + 146d -1 / 2 +7.36SPM_El+102[C]+154[N]+51.8[Si]+1.4[Mo]-17.7[Cu]
[0013] In the above formula (1), [C], [N], [Si], [Mo], and [Cu] represent the weight % of each element, d represents the average grain size (μm), and SPM_El represents the difference in elongation (%) before and after skin pass milling.
[0014] In addition, the Ω value represented by the following formula (2) of the austenitic stainless steel according to the present invention can be 2500 or more.
[0015] Formula (2): Ω=YS×El-500×([Ni]+[Cr]+[Cu]+[Mn])
[0016] In the above formula (2), [Ni], [Cr], [Cu], and [Mn] represent the weight % of each element, YS represents the yield strength (MPa), and El represents the elongation (%).
[0017] In addition, the austenite stability parameter (ASP) value represented by the following formula (3) of the austenitic stainless steel according to the present invention may be -5 to 12.
[0018] Formula (3): ASP value = 551-462×([C]+[N])-9.2×[Si]-8.1×[Mn]-13.7×[Cr]-29×([Ni]+[Cu])-18.5×[Mo]
[0019] In the above formula (3), [C], [N], [Si], [Mn], [Cr], [Ni], [Cu], and [Mo] represent the weight % of each element.
[0020] In addition, the Π value represented by the following formula (4) of the austenitic stainless steel according to the present invention can be 6000 or more.
[0021] Formula (4): Π=100×FCRR (Final Cold Rolling Ratio, %) + 100×ASP (Austenite stability parameter) + CAT (Cold annealing temperature, °C)
[0022] In the above formula (4), FCRR represents the reduction ratio during cold rolling before final cold annealing, ASP represents the value of formula (3), and CAT represents a value defined by the temperature of the final cold annealed steel material.
[0023] In addition, when the total thickness of the austenitic stainless steel according to the present invention is t, the average grain size (d) value of the thickness center portion in the transverse direction (TD) plane may be 3 μm or more and 10 μm or less.
[0024] In addition, the thickness t may be 0.4-2.0 mm.
[0025] In addition, in the austenitic stainless steel according to the present invention, when the thickness center portion of the transverse (TD) plane is analyzed using an electron backscatter diffraction (EBSD) spectrometer, the martensite fraction (%) of the cold rolled material may be 60% or more.
[0026] In addition, in the austenitic stainless steel according to the present invention, when the thickness center portion of the transverse (TD) plane is analyzed using an electron backscatter diffraction (EBSD) spectrometer, the fraction (%) of the misorientation angle (Misorientation Angle) of 15° or more after cold annealing can be 95% or more.
[0027] In addition, the pitting potential value of the austenitic stainless steel according to the present invention in a 30° C., 3.5% NaCl solution can be 250 mV or more.
[0028] In addition, the surface roughness (Ra) of the austenitic stainless steel according to the present invention when stretched by 30% can be 0.50 μm or less, the surface roughness (Ra) when stretched by 20% can be 0.36 μm or less, and the surface roughness (Ra) when stretched by 10% can be 0.25 μm or less.
[0029] In addition, the aging cracking limit drawing ratio (Limited Drawing Ratio) of the austenitic stainless steel according to the present invention may be 2.0 or more.
[0030] Furthermore, the average earing height of the austenitic stainless steel during drawing according to the present invention can be 2.2 mm or less.
[0031] In addition, the austenitic stainless steel according to the present invention can generate no surface cracks at the bent portion after a 180° bending test.
[0032] (III) Beneficial effects
[0033] According to one embodiment of the present invention, an ultrafine grain 300 series stainless steel having excellent hardness can be provided.
[0034] According to one embodiment of the present invention, an ultrafine grain 300 series stainless steel satisfying both high strength and high ductility can be provided.
[0035] According to one embodiment of the present invention, an austenitic stainless steel having no surface cracks in a bent portion and excellent surface roughness can be provided by ultrafine grain manufacturing technology that achieves good bending formability and surface properties of a bent portion. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a graph showing Σ values and Ω values of Examples and Comparative Examples.
[0037] Figure 2 This is a photograph showing the microstructure of an embodiment in which the Π value satisfies 6000 or more.
[0038] Figure 3 This is a photograph showing an unannealed zone in the fine structure of Comparative Example 1 in which the Π value is less than 6000.
[0039] Figure 4The photographs show that the martensite (red color) fraction (%) is 91.5% and 73.5% when the phase fraction (Phase Fraction) of the thickness center portion of the transverse (TD) plane of the cold-rolled material of the example is analyzed using an electron backscatter diffraction (EBSD) spectrum analyzer.
[0040] Figure 5 This is a photograph showing that the martensite (red) fraction (%) is 48.5% when the phase fraction in the thickness center portion of the transverse (TD) plane of the cold-rolled material of the comparative example is analyzed using an electron backscatter diffraction (EBSD) spectrum analyzer.
[0041] Figure 6 The photographs show that the fractions (%) of misorientation angles of 15° or more are 96% and 96.5% when analyzing the thickness center of the transverse (TD) plane of the cold annealed material of the example using an electron backscatter diffraction (EBSD) spectrometer.
[0042] Figure 7 This is a photograph showing that the fraction (%) of misorientation angles of 15° or more is 92.9% when analyzing the thickness center of the transverse (TD) plane of the cold annealed material of the comparative example using an electron backscatter diffraction (EBSD) spectrometer. Misorientation angles less than 15° correspond to red.
[0043] Figure 8 This is a photograph showing the average grain size in the thickness center portion of the transverse (TD) plane of the steel material with a thickness of 0.4 to 2.0 mm produced in the Examples.
[0044] Fig. 9 This is a photograph showing the average grain size of the thickness center portion of the transverse (TD) plane of a 0.4-2.0 mm steel material produced in a comparative example.
[0045] Fig.10 Graph showing the surface roughness Ra (μm) values of Example and Comparative Example 2 according to the tensile strain rate.
[0046] Fig.11 The photographs show the shapes of the surface roughness Ra (μm) according to the tensile strain rate of Examples and Comparative Examples.
[0047] Fig.12 The photographs show the ear heights after drawing in Examples and Comparative Examples. Best Mode for Carrying Out the Invention
[0048] The austenitic stainless steel according to one embodiment of the present invention may contain, in terms of weight %, 0.04-0.07% C, 0.3-0.6% Si, 0.5-1.5% Mn, 0.1-0.4% Cu, 0.05-0.2% Mo, 8.0-9.0% Ni, 18.0-19.0% Cr, and 0.02-0.05% N, and may contain the remainder of Fe and inevitable impurities, and the Σ value of the austenitic stainless steel represented by the following formula (1) may be 180 or more and 240 or less.
[0049] Formula (1): Σ = 105 + 146d -1 / 2 +7.36SPM_El+102[C]+154[N]+51.8[Si]+1.4[Mo]-17.7[Cu]
[0050] In the above formula (1), [C], [N], [Si], [Mo], and [Cu] represent the weight % of each element, d represents the average grain size (μm), and SPM_El represents the difference in elongation (%) before and after temper rolling. DETAILED DESCRIPTION
[0051] Below, the preferred embodiment of the present invention is described. However, the embodiment of the present invention can be modified into various other forms, and the technical idea of the present invention is not limited to the embodiment described below. In addition, the embodiment of the present invention is provided to more completely describe the present invention to those skilled in the art.
[0052] The terms used in this application are only used to illustrate specific examples. Therefore, unless the context clearly indicates that it must be singular, the singular expression includes the plural expression. In addition, it should be noted that the terms "comprise", "include" or "have" used in this application are used to clearly specify the existence of the features, steps, functions, constituent elements or their combinations recorded in the specification, and are not used to preclude the existence of other features or steps, functions, constituent elements or their combinations.
[0053] In addition, unless otherwise defined, all terms used in this specification should be deemed to have the same meaning as that generally understood by a person skilled in the art of the art to which the present invention belongs. Therefore, in this specification, unless otherwise clearly defined, specific terms should not be interpreted in an overly ideal or formal sense. In this specification, unless otherwise clearly stated in the context, a singular expression includes a plural expression.
[0054] In addition, with respect to the words "approximately", "substantially", etc. in this specification, when the allowable errors of manufacturing and materials inherent in the mentioned meaning are proposed, they are used in the sense of that value or close to that value, and are used to prevent unscrupulous infringers from illegally using the mentioned exact or absolute numerical values to help understand the disclosure of the present invention.
[0055] According to an example of the present invention, the austenitic stainless steel may include, by weight%, C: 0.04-0.07%, Si: 0.3-0.6%, Mn: 0.5-1.5%, Cu: 0.1-0.4%, Mo: 0.05-0.2%, Ni: 8.0-9.0%, Cr: 18.0-19.0%, N: 0.02-0.05%, and may contain the remainder of Fe and inevitable impurities.
[0056] The reasons for limiting the alloy composition are described in detail below.
[0057] The content of carbon (C) may be 0.04-0.07%.
[0058] C is an element that stabilizes the austenite phase. Considering this, the amount of C added may be 0.04% or more. However, when the C content is too high, chromium carbides may be formed during low-temperature annealing, so that the problem of reducing grain boundary corrosion resistance may occur. Considering this, the upper limit of the C content may be limited to 0.07%.
[0059] The content of silicon (Si) may be 0.3-0.6%.
[0060] Si is a component added as a deoxidizer in the steelmaking step, and forms Si oxide on the passivation film during the bright annealing process, thereby having the effect of improving the corrosion resistance of the steel. Considering this, the amount of Si added can be 0.3% or more. However, when the content of Si is too high, the problem of reducing the ductility of the steel may occur. Considering this, the upper limit of the content of Si can be limited to 0.6%.
[0061] The content of manganese (Mn) may be 0.5-1.5%.
[0062] Mn is an element that stabilizes the austenite phase. Considering this, the amount of Mn added may be 0.5% or more. However, when the content of Mn is too high, the problem of reduced corrosion resistance may occur. Considering this, the upper limit of the content of Mn may be limited to 1.5%.
[0063] The content of nickel (Ni) may be 8.0-9.0%.
[0064] Ni is an element that stabilizes the austenite phase and has the effect of softening the steel. Considering this, the amount of Ni added can be 8.0% or more. However, when the content of Ni is too high, the problem of increased cost may occur. Considering this, the upper limit of the content of Ni can be limited to 9.0%.
[0065] The content of chromium (Cr) may be 18.0-19.0%.
[0066] Cr is a main element for improving the corrosion resistance of stainless steel. Considering this, the addition amount of Cr can be 18.0% or more. However, when the content of Cr is too high, problems such as hardening of the steel and suppression of strain-induced martensitic transformation during cold rolling may occur. Considering this, the upper limit of the content of Cr can be limited to 19.0%.
[0067] The content of copper (Cu) may be 0.1-0.4%.
[0068] Cu is an element that stabilizes the austenite phase. Considering this, the amount of Cu added can be 0.1% or more. However, when the Cu content is too high, the corrosion resistance of the steel may be reduced and the cost may increase. Considering this, the upper limit of the Cu content can be limited to 0.4%.
[0069] The content of nitrogen (N) may be 0.02-0.05%.
[0070] N is an element that stabilizes the austenite phase and improves the strength of the steel. Considering this, the amount of N added may be 0.02% or more. However, when the N content is too high, problems such as hardening of the steel and reduction of hot workability may occur. Considering this, the upper limit of the N content may be limited to 0.05%.
[0071] The content of molybdenum (Mo) may be 0.05-0.2%.
[0072] Mo has the effect of improving corrosion resistance and processability. Considering this, the amount of Mo added may be 0.05% or more. However, when the content of Mo is too high, the problem of increased cost may occur. Considering this, the upper limit of the content of Mo may be limited to 0.2%.
[0073] The remaining component is iron (Fe). However, in the conventional manufacturing process, undesirable impurities may inevitably be mixed from the raw materials or the surrounding environment, so these impurities cannot be excluded. These impurities are well known to technicians in the conventional manufacturing process, so all of them are not specifically mentioned in this specification.
[0074] In the austenitic stainless steel according to one example of the present invention, in addition to controlling the composition ratio of the alloy components, the following may be defined.
[0075] In one example of the present invention, the Σ value represented by the following formula (1) may be 180 or more and 240 or less.
[0076] Formula (1): Σ = 105 + 146d -1 / 2 +7.36SPM_El+102[C]+154[N]+51.8[Si]+1.4[Mo]-17.7[Cu]
[0077] Σ is an index that indicates the hardness of a material. The larger the Σ value, the greater the hardness.
[0078] In the above formula (1), [C], [N], [Si], [Mo], and [Cu] represent the weight % of each element, d represents the average grain size (μm), and SPM_El represents the difference in elongation (%) before and after temper rolling.
[0079] According to one example of the present invention, SPM_El may be 0.01 to 1.2.
[0080] Temper rolling can be done to improve the steel's glossiness and secure the coil's shape.
[0081] In one example of the present invention, the Ω value represented by the following formula (2) may be 2500 or more.
[0082] Formula (2): Ω=YS×El-500×([Ni]+[Cr]+[Cu]+[Mn])
[0083] Ω is an index indicating high strength-high ductility. The larger the Ω value, the greater the product of strength and ductility.
[0084] In the above formula (2), [Ni], [Cr], [Cu], and [Mn] represent the weight % of each element, YS represents the yield strength (MPa), and El represents the elongation (%).
[0085] The YS value and the El value represent values obtained by subjecting a JIS 13B tensile test piece to a tensile test at room temperature using a crosshead in a range of 10 mm / min to 20 mm / min.
[0086] In one example of the present invention, the value of the austenite stability parameter (ASP) represented by the following formula (3) may be -5 to 12.
[0087] Formula (3): ASP value = 551-462×([C]+[N])-9.2×[Si]-8.1×[Mn]-13.7×[Cr]-29×([Ni]+[Cu])-18.5×[Mo]
[0088] In the above formula (3), [C], [N], [Si], [Mn], [Cr], [Ni], [Cu], and [Mo] represent the weight % of each element.
[0089] When the ASP value is not within the range of -5 to 12, the material undergoes an excessive phase change during a tensile test, thereby failing to satisfy the desired elongation of the present invention.
[0090] In one example of the present invention, the Π value represented by the following formula (4) may be 6000 or more.
[0091] Formula (4): Π=100×FCRR (final cold rolling rate, %) + 100×ASP (austenite stability parameter) + CAT (cold annealing temperature, °C)
[0092] Π is an index representing the degree of recrystallization completion. The larger the Π value, the higher the degree of recrystallization.
[0093] In the above formula (4), FCRR represents the reduction ratio during cold rolling before final cold annealing, ASP represents the value of formula (3), and CAT represents a value defined by the temperature of the final cold annealed steel material.
[0094] According to an example of the present invention, the average grain size d may be greater than or equal to 3 μm and less than or equal to 10 μm.
[0095] The average grain size indicates the average grain size of the thickness center portion of the transverse (TD) plane when the total thickness of the steel material is t, the average indicates the average value of the values measured at any five positions, and the center portion indicates 1 / 4t to 3 / 4t when the total thickness of the steel material is t.
[0096] According to one example of the present invention, t may be 0.4-2.0 mm. In the case of kitchen and building material parts, materials with a thickness of 0.4-2.0 mm are widely used, and according to the present invention, stainless steel having excellent hardness within the corresponding thickness range and high strength-high ductility can be provided.
[0097] In one example of the present invention, when an electron backscatter diffraction (EBSD) spectrometer is used to analyze the thickness center portion of the transverse (TD) plane, the martensite fraction (%) of the cold-rolled material can be greater than 60%, and after cold annealing, the fraction (%) of orientation difference angles greater than 15° can be greater than 95%.
[0098] When the misorientation angle is 15° or more, it means that recrystallization has occurred after cold annealing, and when the misorientation angle is less than 15°, it is considered that the difference in orientation angle is small and recrystallization has not occurred.
[0099] The average grain size (d), the martensite fraction (%) of the cold-rolled material, and the fraction (%) of the misorientation angle of 15° or more after cold annealing in the present invention are measured by analyzing the orientation of the thickness center using an electron backscatter diffraction (EBSD) spectrometer model e-Flash FS.
[0100] The pitting potential is a critical potential at which corrosion occurs in the form of holes in a passivated metal material, and the result of measuring the potential (pitting potential) at which pitting occurs by immersing an austenitic stainless steel according to an embodiment of the present invention in a NaCl solution and applying a potential can be 250 mV or more. The temperature of the NaCl solution can be 30° C., and the concentration can be 3.5%.
[0101] The surface roughness (Ra) of the austenitic stainless steel according to one example of the present invention may be 0.50 μm or less when stretched by 30%, 0.36 μm or less when stretched by 20%, and 0.25 μm or less when stretched by 10%.
[0102] According to one embodiment of the present invention, when a punch size of Φ50 mm and a disc size of Φ100 mm are used in the drawing process, the aging crack limit drawing ratio can be greater than 2.0. In addition, the average earing height can be less than 2.2 mm.
[0103] The aging crack limit drawing ratio is a limit drawing ratio at which aging cracks do not occur, and indicates a ratio between the maximum diameter of a material and the punch diameter during drawing.
[0104] The average ear height represents the average value of the sum of the maximum ear height (H) from the bottom after drawing minus the sum of the minimum ear height (h).
[0105] According to an embodiment of the present invention, after a 180° bending test, no surface cracks may be generated at the bent portion.
[0106] Next, a method for producing austenitic stainless steel according to an example of the present invention will be described in detail.
[0107] A method for manufacturing austenitic stainless steel according to an example of the present invention may include the following steps: manufacturing a slab, wherein the slab contains, by weight%, C: 0.04-0.07%, Si: 0.3-0.6%, Mn: 0.5-1.5%, Cu: 0.1-0.4%, Mo: 0.05-0.2%, Ni: 8.0-9.0%, Cr: 18.0-19.0%, N: 0.02-0.05%, and a balance of Fe and inevitable impurities; hot rolling the slab and performing heat annealing to manufacture a hot-rolled steel sheet; and cold rolling and cold annealing the hot-rolled steel sheet to manufacture a cold-rolled steel sheet.
[0108] The reasons for limiting the composition range of each alloy element are as described above. Hereinafter, the production steps will be described in more detail.
[0109] The thermal annealing may be performed at 1000-1150°C.
[0110] When the thermal annealing temperature is lower than 1000°C, the residual martensite fraction is high, and thus the elongation may be deteriorated. On the other hand, when the thermal annealing temperature exceeds 1150°C, the strength may be reduced due to coarsening of the grains. In view of this, the thermal annealing is performed at 1000-1150°C.
[0111] The cold rolling reduction ratio may be 60% or more.
[0112] When the reduction ratio is less than 60%, the amount of TRIP phase is too low, so the fraction of martensite of the cold rolled material decreases, and the fraction of the retained austenite phase increases. As the amount of strain-induced martensite decreases, the proportion of the reversely transformed austenite phase by subsequent low-temperature annealing decreases, and the fraction of the retained austenite phase that has not been transformed into martensite is high, making it difficult to ensure ultrafine grains.
[0113] The cold annealing may be performed at 800-950°C.
[0114] When the cold annealing temperature is lower than 800°C, recrystallization does not occur sufficiently, so the elongation decreases. On the other hand, when the cold annealing temperature exceeds 950°C, the particles coarsen, making it difficult to form ultrafine grains of 3 μm to 10 μm or less, so there may be a problem that surface cracks are generated at the bending part of the austenitic stainless steel and the surface roughness deteriorates. In view of this, the cold annealing is performed at 800-950°C.
[0115] In addition, the manufacturing method may be a method for manufacturing austenitic stainless steel, including the step of temper rolling the cold-rolled steel sheet.
[0116] The SPM_El is the difference in elongation (%) before and after skin pass rolling, and the SPM_El is set to 0.01 to 1.2.
[0117] Below, the present invention is described in more detail by examples. However, the description of these examples is only used to illustrate the implementation of the present invention, and the present invention is not limited by the description of these examples. This is because the scope of the present invention is determined by the contents recorded in the claims and the contents reasonably derived therefrom.
[0118] {Example}
[0119] The slabs having the composition shown in Table 1 below were hot rolled, then heat annealed at 1000-1150°C, and cold rolled at a reduction ratio of 60% or more at room temperature. Then, cold annealing was performed in the range of 800-950°C to produce cold annealed materials.
[0120] [Table 1]
[0121]
[0122] The following Table 2 shows the values of formulas (1) to (4) according to the component values in Table 1, SPM_El (Skin Pass Mill Elongation, %), FCRR (final cold rolling rate, %), CAT (cold annealing temperature, °C) and YS (MPa) × El (%) values.
[0123] [Table 2]
[0124]
[0125] The YS value and El value indicate values obtained by subjecting a JIS 13B tensile test piece to a tensile test at room temperature using a crosshead at a speed ranging from 10 mm / min to 20 mm / min.
[0126] The cold annealed material was made into a test piece with a thickness of 0.4-2.0 mm. Then, the average grain size (d) of the thickness center of the test piece, pitting potential (mV), whether surface cracks were generated at the bending part after a 180° bending test (the curvature R value of the bending part was the same as the material thickness), and the surface roughness at different tensile strain rates in a uniaxial tensile test were measured, and then shown in Table 3 below.
[0127] [Table 3]
[0128]
[0129] The average grain size (d) at the center of the thickness refers to the average grain size (d) at the center of the thickness of the transverse (TD) plane of a test piece having a thickness of 0.4 to 2.0 mm.
[0130] The average grain size (d) of the present invention is measured by analyzing the orientation of the center of the thickness using an electron backscatter diffraction (EBSD) spectrometer model e-Flash FS.
[0131] The pitting potential is the value of the potential at which pitting occurs when the sample is immersed in a 3.5% NaCl solution at a temperature of 30°C and a potential is applied.
[0132] The tensile strain rate value indicates a value obtained by subjecting a JIS 13B tensile test piece to a uniaxial tensile test at a crosshead speed of 10 to 20 mm / min.
[0133] Whether bending cracks occur is determined by performing a 180° bending test in which the curvature R value of the bent portion is made equal to the material thickness and bending is performed once.
[0134] The average ear height according to one example of the present invention is shown in Table 4 below.
[0135] [Table 4]
[0136]
[0137] The average ear height represents the average value of the sum of the maximum height (H) from the bottom to the ear after drawing minus the sum of the minimum height (h) of the ear. H represents the maximum height, h represents the minimum height, and ear 1 to ear 4 are the order arbitrarily assigned to each ear.
[0138] The age crack limit drawing ratio (LDR) value and the average ear height indicate the age crack limit drawing ratio and the average ear height when the drawing process is performed using a punch size of Φ50 mm and a disc size of Φ100 mm.
[0139] Referring to Table 1 and Table 2, in Examples 1 to 6, the Σ value of formula (1) satisfies the range of greater than -180 and less than 240, and the Ω value of formula (2) satisfies the range of greater than 2500, so excellent hardness and high strength-high ductility can be achieved.
[0140] Referring to Tables 1 to 3, in Examples 1 to 6, the ASP values of formula (3) all satisfy the range of -5 to 12, and the Π value of formula (4) satisfies the range of above 6000, so no surface cracks are generated after the 180° bending test.
[0141] Referring to Table 3, in Examples 1 to 6, the average grain size (d) value of the thickness center portion of the material in the range of 0.4-2.0 mm satisfies the range of 3 μm or more and 10 μm or less, and after the uniaxial tensile test, the surface roughness (Ra) when stretched by 30% is 0.50 μm or less, the surface roughness (Ra) when stretched by 20% is 0.36 μm or less, and the surface roughness (Ra) when stretched by 10% is 0.25 μm or less. In addition, the pitting potential value satisfies the range of 250 mV or more.
[0142] On the other hand, the Σ values of Comparative Examples 2 to 4 were less than 180, and thus could not satisfy the hardness of the present invention. This can be confirmed in Table 2.
[0143] In addition, the Ω values of Comparative Examples 2 to 7 were less than 2500, and thus the high strength and high ductility of the present invention could not be simultaneously satisfied. This can be confirmed in Table 2.
[0144] In addition, Comparative Examples 3 to 8 are not within the ASP value range defined in the present invention. In Comparative Examples 5 to 8, where the ASP value exceeds 12, low elongation is exhibited due to an excessively fast phase transformation rate. In Comparative Examples 2 to 4, where the ASP value is less than -5, ultrafine grains cannot be ensured due to a high fraction of the retained austenite phase. This can be confirmed in Tables 2 and 3.
[0145] In addition, in Comparative Example 1, since the Π value is less than 6000, there is an unannealed zone, and the steel material including the unannealed zone generates bending cracks after the 180° bending test. This can be seen in Tables 2, 3 and Figure 3 In contrast, Figure 2 The microstructure of the example is shown in FIG. 1 , and no banded structure is observed. It can be confirmed that no bending cracks are generated after the 180° bending test.
[0146] In Comparative Examples 6 to 8, since the Ni content was low and an excessive amount of Mn was added, the pitting potential values were low, and thus a problem with corrosion resistance occurred.
[0147] In Comparative Example 2, the d value is 25.2, and the average grain size is coarser than the range of the present invention, so the surface roughness value according to the tensile strain rate is larger. This can be seen in Tables 3 and Figure 6 Confirmed in.
[0148] Figure 1 The ranges of Σ and Ω values of Examples 1 to 6 and Comparative Examples 1 to 8 are shown in FIG. Comparative Examples 2 to 8 do not satisfy both Σ and Ω values. That is, hardness and high strength-high ductility cannot be satisfied at the same time.
[0149] Figure 2 and Figure 3 This is a photograph of the fine structure of the thickness center taken by EBSD. Figure 3 ) shows that there is an unannealed zone in the microstructure. In contrast, Example ( Figure 2 ) shows that there is no unannealed zone in the fine structure. In contrast, it can be confirmed that the austenitic stainless steel according to one example of the present invention is an ultrafine grain particle without a band-shaped unannealed portion.
[0150] Figure 4 and Figure 5 The figure shows the martensite (red) fraction (%) when the phase fraction of the transverse (TD) plane of the cold-rolled material of the embodiment and the comparative example is analyzed by an electron backscatter diffraction (EBSD) spectrometer. Figure 4 ) has a martensite fraction of more than 60%, which is comparable to that of the comparative example ( Figure 5 ) with a martensite fraction of less than 60%.
[0151] Figure 6 and Figure 7 The figure shows the fraction (%) of misorientation angles of 15° or more when the thickness center of the transverse (TD) plane of the cold annealed materials of the examples and comparative examples is analyzed using an electron backscatter diffraction (EBSD) spectrometer. Figure 6 ) has a fraction (%) of 15° or more of the misorientation angle being 95% or more, which is comparable to the comparative example ( Figure 7 ) are compared with the fraction (%) of misorientation angles of 15° or more that are less than 95%. Misorientation angles less than 15° correspond to red.
[0152] Figure 8 and Fig. 9 : is a photograph showing the average grain size of the thickness center portion of the transverse (TD) plane of the steel material with a thickness of 0.4-2.0 mm produced in the embodiment and the comparative example. It can be confirmed that the comparative example ( Fig. 9 ) has an average grain size larger than that of Example ( Figure 8 )’s average grain size.
[0153] Fig.10 : is a graph showing the surface roughness Ra (μm) values after the steel material prepared in Comparative Example 2 was subjected to a uniaxial tensile test at different strain rates at a crosshead speed of 10-20 mm / min, wherein the average grain size of the surface center portion of the steel material prepared in Comparative Example 2 is larger than the average grain size of the embodiment. When the average grain size exceeds the range of the present invention, it can be confirmed that the surface roughness Ra values at different strain rates cannot meet the range of the present invention.
[0154] Fig.11It is a photo showing the shape of the surface roughness Ra (μm) after the uniaxial tensile test at different strain rates at a crosshead speed of 10-20 mm / min for the embodiment and the comparative example. The units of the x-axis and the y-axis are mm, and the unit of the height corresponds to μm. In the comparative example, it can be confirmed that the height increases with the application of strain, so that the surface roughness is higher. Different from this, in the embodiment, it can be confirmed that even if strain is applied, the surface roughness of the embodiment is lower than the surface roughness of the comparative example.
[0155] Fig.12 This is a photograph showing the ear height after drawing (punch size is Φ50 mm, disc size is Φ100 mm). The average ear height represents the average value of the sum of the maximum ear height (H) from the bottom to the ear after drawing minus the sum of the minimum ear height (h). It can be confirmed that the average ear height of the example is smaller than the average ear height of the comparative example.
[0156] As described above, exemplary embodiments of the present invention have been described, but the present invention is not limited thereto, and those skilled in the art will appreciate that various changes and modifications may be made without departing from the concept and scope of the claims.
[0157] Industrial Applicability
[0158] According to the present invention, an ultrafine grain 300 series stainless steel that satisfies both high strength and high ductility can be provided, and by realizing ultrafine grain manufacturing technology that achieves bending formability and good surface properties of the bent portion, an austenitic stainless steel having no surface cracks in the bent portion and excellent surface roughness can be provided, thus having industrial applicability.
Claims
1. An austenitic stainless steel, comprising, by weight%, C: 0.04-0.07%, Si: 0.3-0.6%, Mn: 0.5-1.5%, Cu: 0.1-0.4%, Mo: 0.05-0.2%, Ni: 8.0-9.0%, Cr: 18.0-19.0%, N: 0.02-0.05%, and the balance Fe and unavoidable impurities, The austenitic stainless steel has a Σ value represented by the following formula (1) of 180 or more and 240 or less. Formula (1): Σ = 105 + 146d -1 / 2 +7.36SPM_El+102[C]+154[N]+51.8[Si]+1.4[Mo]-17.7[Cu] In the above formula (1), [C], [N], [Si], [Mo], and [Cu] represent the weight % of each element, d represents the average grain size in μm, and SPM_El represents the difference in elongation before and after skin pass rolling in %.
2. The austenitic stainless steel according to claim 1, wherein: The Ω value of the austenitic stainless steel represented by the following formula (2) is 2500 or more, Formula (2): Ω=YS×El-500×([Ni]+[Cr]+[Cu]+[Mn]) In the above formula (2), [Ni], [Cr], [Cu], and [Mn] represent the weight % of each element, YS represents the yield strength in MPa, and El represents the elongation in %.
3. The austenitic stainless steel according to claim 1, wherein: The austenite stability parameter (ASP) value of the austenitic stainless steel represented by the following formula (3) is -5 to 12, Formula (3): ASP value = 551-462×([C]+[N])-9.2×[Si]-8.1×[Mn]-13.7×[Cr]-29×([Ni]+[Cu])-18.5×[Mo] In the above formula (3), [C], [N], [Si], [Mn], [Cr], [Ni], [Cu], and [Mo] represent the weight % of each element.
4. The austenitic stainless steel according to claim 1, wherein: The austenitic stainless steel has a Π value represented by the following formula (4) of 6000 or more. Formula (4): Π=100×FCRR (final cold rolling rate, %) + 100×ASP (austenite stability parameter) + CAT (cold annealing temperature, °C) In the above formula (4), FCRR represents the reduction ratio during cold rolling before final cold annealing, ASP represents the value of formula (3), and CAT represents a value defined by the temperature of the final cold annealed steel material.
5. The austenitic stainless steel according to claim 1, wherein: When the total thickness of the steel material is t, the average grain size (d) value of the thickness center portion in the transverse direction (TD) plane is 3 μm or more and 10 μm or less.
6. The austenitic stainless steel according to claim 1, wherein: The t is 0.4-2.0 mm.
7. The austenitic stainless steel according to claim 1, wherein: After cold rolling, the martensite fraction (%) in the thickness center portion in the transverse direction (TD) plane is 60% or more.
8. The austenitic stainless steel according to claim 1, wherein: After cold annealing, the fraction (%) of misorientation angles of 15° or more in the thickness center portion in the transverse direction (TD) plane is 95% or more.
9. The austenitic stainless steel according to claim 1, wherein: The pitting potential value of the austenitic stainless steel in a 30° C., 3.5% NaCl solution is greater than 250 mV.
10. The austenitic stainless steel according to claim 1, wherein: The surface roughness (Ra) of the austenitic stainless steel when stretched by 30% is 0.50 μm or less, the surface roughness (Ra) when stretched by 20% is 0.36 μm or less, and the surface roughness (Ra) when stretched by 10% is 0.25 μm or less.
11. The austenitic stainless steel according to claim 1, wherein: The austenitic stainless steel has an aging crack limit drawing ratio of 2.0 or more.
12. The austenitic stainless steel according to claim 1, wherein: The average ear height of the austenitic stainless steel during drawing is 2.2 mm or less. The average ear height refers to the average value of the sum of the maximum ear height (H) from the bottom to the ear after drawing minus the sum of the minimum ear height (h).
13. The austenitic stainless steel according to claim 1, wherein: The austenitic stainless steel does not generate surface cracks at the bent portion after a 180° bending test.
Citation Information
Cited By
Short-process preparation method for continuous casting of 304 stainless steel thin strip
CN120888735A
